Analisis Dampak Game Online Mobile Legend Terhadap Sikap, Pengetahuan, dan Keterampilan Peserta didik Kelas V - Amalia, Nur; Aunillah Naya, Natana (Jurnal Elementaria Edukasia, 2023)
Online games are a sign of fast-growing technological advances. This research aims to 1. Analyze the knowledge gained by students from playing online mobile legend games, 2. Analyze attitudes acquired by students from playing mobile legend online games, 3. Analyze skills acquired obtained by students from playing mobile legend online games. This type of research uses qualitative methods, data collection techniques in this study are observation, interviews, and documentation. The data analysis technique used is Miles & Huberman's data validation with steps data collection, data reduction, data display, conclusion drawing/ verification. The validity of the data in this study used two types of triangulations, namely source triangulation and technical triangulation. The results of this study are 1. Knowledge gained by students from playing mobile legend online games that students when playing mobile legend games get new vocabulary, namely vocabulary in the form of push, kill, ulti, good game, buff, lord, minion, turtle , victory, defeat etc., 2. Attitudes obtained by students from playing mobile legend online games in terms of the emotional attitude of students have not been able to control their behavior as evidenced by delaying worship, eating, parental orders, besides that it is not uncommon for them to say dirty words when you get team members who are not good at playing. However, emotional attitudes such as speaking harshly are not addressed when they interact with older people. Besides that, playing games for 3-5 hours also inhibits other activities, 3. The skills acquired by students from playing mobile legend online games students are able to interact with older people because in the mobile legend game there is a voice feature where they can talk to team members, this is not realized that it is also included in social interaction, besides that they also carry out direct social interactions such as reciting the Koran, and playing.